Role of human assets in measuring firm performance and its implication for firm valuation - Moinak Maiti; Darko Vuković (Journal of Economic Structures, 2020)
The purpose of the study is to evaluate the role of human asset in firm performance and its implication for firm valuation. To do so a modified five-factor model with human asset designed for capturing the size, value, profitability and investment in average portfolio returns that performs better than both Fama-French (1993) three- and Fama-French (2015) five-factor model. Study redefines CMA factors as CvMAv that includes human assets in it. The main problem with the modified five-factor model with human asset is the microcap with conservative investment stocks whose returns behave like that low-value unprofitable firms.
Keywords: G12; 330; Human asset; Factor models; Asset Pricing; Risk